Empowering Communities: The Impact of Digital Health Education Modules on Disaster Preparedness - Nina Putri Calisanie, Nyayu; Mastriyani, Nindi; Permana, Septa; Ramdani, Ramdani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: The primary aim is to raise catastrophe awareness and preparedness, especially in disaster-prone areas. Health education and consulting by nurses using digital media like modules to teach disaster planning, first aid, and recovery can assist communities recover from disasters. Method: This research is a Quasi Experiment research with a research design. Quasi-Experimental Two Group pretest-posttest design . The number of respondents was 60. Inclusion criteria in this study were aged 17-35 years . Results: Mann-Whitney Test Analysis . The average value of the intervention group was greater than the control group. The Sig. (2-tiled) value shows that there is a significant influence of the Digital Module intervention on the level of disaster preparedness in the community with a p-value of 0.000 <0.05. Conclusion: In this study, it can be concluded that the Digital Module has an influence on increasing community preparedness in the intervention and control groups, there is a significant difference.